Sosial Entrepreneur : Upaya Menumbuhkan Minat Wirausaha bagi Tenaga Kerja Imigran Indonesia di Ulu Langat Malaysia - Lestari, Anggia Ayu; Liantifa, Melifia; Halimah, Putri; Mufid, Inzanul (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
This Community Service Activity (PKM) was carried out by STIE Sakti Alam Kerinci lecturers in Ulu Langat Malaysia where there are a lot of immigrant workers, especially workers from the Kerinci Regency and Sungai Full City areas who are members of the HKKN (National Kerinci Family Association) in Malaysia. This service aims to provide socialization regarding the importance of entrepreneurship even though most of the workforce already works in Malaysia. In this modern era, creativity and innovation are very necessary in various business fields to achieve competitive advantage. So, with this service activity, the aim is to increase the entrepreneurial spirit of the workforce so that they can increase family income, provide an understanding of creativity and innovation in entrepreneurship to immigrant workers in Kuala Lumpur, Malaysia. This community service activity is carried out by providing lecture materials and provide examples of businesses that can increase immigrant workers' references in entrepreneurship. The material presented is relevant to current technological developments, so it is hoped that immigrant workers can change their mindset about the importance of being an entrepreneur in this modern era.